2017
DOI: 10.1002/jcla.22281
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of circRNA hsa_circ_0003159 in gastric cancer and its clinical significance

Abstract: All of the results suggest that hsa_circ_0003159 may be a potential cancer marker of patients with gastric cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
83
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(90 citation statements)
references
References 17 publications
5
83
0
Order By: Relevance
“…In addition to being a microRNA “sponge” or regulator of gene transcription [34], circRNAs not only can produce pseudogenes to alter the genomic DNA composition [18, 20, 35] but also possess a protein translation function [19]. Moreover, as prevalent molecules in eukaryotic cells, circRNAs are expressed abnormally in many types of cancer diseases and are closely related to the occurrence and development of cancer [32, 36, 37]. This evidence reveals that circRNAs can provide potential targets for the clinical diagnosis and prognosis of cancer.…”
Section: Discussionsupporting
confidence: 47%
“…In addition to being a microRNA “sponge” or regulator of gene transcription [34], circRNAs not only can produce pseudogenes to alter the genomic DNA composition [18, 20, 35] but also possess a protein translation function [19]. Moreover, as prevalent molecules in eukaryotic cells, circRNAs are expressed abnormally in many types of cancer diseases and are closely related to the occurrence and development of cancer [32, 36, 37]. This evidence reveals that circRNAs can provide potential targets for the clinical diagnosis and prognosis of cancer.…”
Section: Discussionsupporting
confidence: 47%
“…The hsa_circ_0003159 levels were first detected in 108 paired gastric cancer tissues and adjacent nontumorous tissues from surgical patients with gastric cancer. Compared with paired adjacent non-tumorous tissues, hsa_circ_0003159 expression was significantly down-regulated in gastric cancer tissues and significantly negatively associated with gender, distal metastasis, and tumor-node-metastasis stage [34]. Similarly, hsa_circ_0014717 was significantly down regulated as well in gastric cancer tissues and related to tumor stage, distal metastasis, tissue carcinoembryonic antigen and carbohydrate antigen 19-9 expression [35].…”
Section: Correlation Of Circrnas To Gastric Cancersupporting
confidence: 46%
“…Zhuang et al () report that hsa_circ_0005836 was significantly down‐regulated in the peripheral blood mononuclear cells, serving as a novel potential biomarker for pulmonary tuberculosis infection(Zhuang et al, ). In gastric cancer tissues, Tian, Chen, Li, and Xiao () reported that hsa_circ_0003159 expression was significantly down‐regulated, acting as a potential cancer marker of patients with gastric cancer. In breast cancer, Zhang et al () reported circulating circular RNA hsa_circ_0001785 was up‐regulated in plasma and had better diagnostic accuracy (AUC = 0.784) (Yin et al, ).…”
Section: Discussionmentioning
confidence: 99%